Fine Needle Aspiration Versus Open Biopsy for Testicular Sperm Recovery in Infertile Azoospermic Patients - Ali, Salah A; Al-Najjar, Suhel (Diyala Journal of Medicine, 2019)
Background and Objectives: This study aimed to develop a predictive model for sperm retrieval rate (SRR) sperm recovery by testicular fine-needle aspiration (TESA) & compare with (SRR) obtained by per cutanuose open biopsy sperm aspiration (PSA) correlating with hormonal parameters. Materials and Methods: This is a prospective study for sample obtained from 45 male patients during the period from January 2011 to March2012.Clinical, paraclinical, and histological information of patients were gathered. All patients underwent both TESA and PSA in a single operation. Predictors of SRR by TESA were identified comparing with predictive outcome of PSA. Statistical Analysis Used: Categorical and continuous variables were compared using independent t test and -chi-square test. Logistic regression model was applied to develop a predictive model for SRR by TESA & PSA outcome. Results: Sperm retrieval rate for TESA and PSA was 42.2% and 48.8%, respectively (P = 0.03).Regarding age group is more common in 4th (50.3%), while 3rd & 5th dacedes each of them (20%). The duration of infertility were variable ranging from (10-20) years. Testis volume, luteinizing hormone, prolactin, and testosterone did not differ between patients. Conclusions: Serum FSH and testicular pathology were predictors of SRR by TESA. Patients with FSH < 23 IU/l and/or testicular pathology of hypospermatogenesis had comparable SRR by TESA versus PSA.